2016
DOI: 10.1556/066.2016.45.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing sucrose with tagatose and isomaltulose in Mandarin orange marmalade on rheology, colour, antioxidant activity, and sensory properties

Abstract: The aim of this study was to make mandarin orange marmalades, in which sucrose is replaced by sweeteners, such as tagatose and isomaltulose, which are non-cariogenic and have a low glycemic index. Analyses of rheology, colour, antioxidant activity, microbiology, and sensory properties were carried out on marmalades on their fi rst day, and after 90, 180, and 360 days of storage. The results showed that marmalades made with healthy sweeteners had a less elastic character and were thinner in consistency than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Rubio‐Arraez, Capella, Ortola, et al. (2016) developed mandarin orange marmalades by replacing sucrose with natural sweeteners (tagatose and isomaltulose) in different proportions. The results showed that the marmalades made with bulk sweeteners, when compared to those made with sucrose, obtained a less elastic character and thinner consistency.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rubio‐Arraez, Capella, Ortola, et al. (2016) developed mandarin orange marmalades by replacing sucrose with natural sweeteners (tagatose and isomaltulose) in different proportions. The results showed that the marmalades made with bulk sweeteners, when compared to those made with sucrose, obtained a less elastic character and thinner consistency.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies (Table 3) have evaluated the effects of natural bulk sweeteners on the sensory aspects of jams, jellies, and marmalades (Benedek et al., 2020; Farias et al., 2019; Minh, 2020; Naknaen & Itthisoponkul, 2015; Özbek et al., 2019; Rubio‐Arraez, Capella, Castelló, et al., 2016; Rubio‐Arraez, Capella, Ortola, et al., 2016, Rubio‐Arraez et al., 2017; Rubio‐Arraez et al., 2018; Viana et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations